Protocole de kyoto : Le cas du secteur résidentiel au Canada? - Gaétan Lafrance (Éditions en environnement VertigO, 2004)
This paper compares unit space heating energy consumptions (USHEC) per household in the Canadian residential sector. The study is based on several surveys conducted by Hydro-Québec and Natural Resource Canada. The approach used to estimate USHEC is the conditional demand analysis (CDA). A comparison between Québec and other Canadian regions seems to show that Québec consumes less energy per household for space heating than other regions in Canada. A further analysis seems to show that the Québec dwelling stock appears more efficient in many aspects. Taking lessons from these comparisons, simple options as lowering heating temperature and a better control of burner can be applied in the Canadian residential sector to reach the Kyoto Protocol.